MEMORY AND OBLIVION VERSUS THE JUGOSLAVIAN HERITAGE. THE CASE OF SERBIAN AND CROATIAN EMIGRANT LITERATURE – PRELIMINARY DIAGNOSIS - Nowak-Bajcar, Sylwia (Porównania, 2014)
Analysis of biographies of writers who, during the recent wars in the former Yugoslavia, have left their homeland, will serve to debate on the problem of the legitimacy of the contemporary category „exile literature”. An attempt to solve this dilemma becomes a starting point for discussion on strategies of remembering and forgetting the heritage of Socialist Federal Republic of Yugoslavia.